نفس سے متعلق اشغال صوفیاء: سیرت طیبہ کی روشنی میں: Sufis delineations regarding NAFS: in the light of Seerat-e- Rasool - Abid Ali,; Dr. Moeen-ud-Din Hashmi, (MEI, 2023)
In the promulgation and origination of Islam, Islmic scholars rendered valuable services in different fields and areas.In these territories primatals of Sufism chains struggled hard for self depuration and heart defecation that imposed positive and deep effects on Muslim Ummah.Sufis edified from all Islamic sources in delineations regarding self. It is obvious that Sufis benifited by Seerahs along with Quarn, hadith and Sharia.Sufis derived diligences as well as delineations from Seerah Rasool ﷺ . In this article a research study is presented how sufis edified from all sources of Islam.